MINIMUM ENGLISH LANGUAGE REQUIREMENTS FOR TAXI-DRIVERS IN DANANG TO COMMUNICATE EFECTIVELY TO THEIR FOREIGN CUSTOMERS - TẠ THỊ LY LY (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
My study presents minimum English language requirements for taxi drivers in Danang to communicate effectively with their foreign customers. The research data are collected by means of questionnaires, observation and interviews with taxi drivers and managers from taxi companies and customers in Danang city. The research uses methods of statistical analysis and comparison to find out the difficulties in communication in English that taxi drivers often face when they contact their foreign customers. Accordingly, suggestions are made on basic knowledge and language requirements (in terms of vocabulary, sentence structures and patterns, and speaking styles, etc.) that a taxi driver needs to know and use to successfully communicate with their customers. This research benefits not only learners themselves but also institutions and ESP teachers in searching materials for their teaching. Therefore, it is a practical and feasible research.